Diffusion and precipitation in alloys - Nabarro, F.R.N. (Institute of Metals, 1947)
A general review is given of recent work on diffusion and precipitation in alloys, with special emphasis on the theoretical mechanism of diffusion, and on the factors governing the shape and size of the precipitate. The effects of internal stresses on diffusion and precipitation, and of precipitation on the mechanical properties, are discussed.
Keywords: precipitation in alloys; diffusion in alloys